LVIS-within-enterprise double-stent technique with coil embolization in the treatment of patients with acutely ruptured intracranial vertebrobasilar artery-dissecting aneurysms - Wu, Qiaowei; Meng, Yuxiao; Chen, Aixia; Xu, Shancai; Wang, Chunlei; Ji, Zhiyong; Qi, Jingtao; Yuan, Kaikun; Shao, Jiang; Shi, Huaizhang; Wu, Pei (Frontiers in Neurology, 2023)
Objective This study aimed to evaluate the feasibility of the low-profile visualized intraluminal support (LVIS)-within-enterprise double-stent technique for patients with acutely ruptured intracranial vertebrobasilar artery-dissecting aneurysms (ari-VBDAs). Methods A total of 30 patients with ari-VBDAs who underwent reconstructive treatment using LVIS-within-enterprise double-stent technique with coil embolization between January 2014 and May 2022 were retrospectively enrolled. Patients' characteristics and clinical and imaging outcomes were reviewed. The functional outcomes were assessed using the modified Rankin scale (mRS). Results A total of 34 ari-VBDAs were identified, including seven (20.6%) basilar artery aneurysms and 27 (79.4%) vertebral artery aneurysms. All aneurysms were successfully treated in the acute phase. In total, six (20.0%) patients experienced in-hospital serious adverse events, including two deaths (6.7%). The median clinical follow-up time of the remaining 28 patients was 20.0 (IQR, 7.3–40.8) months. The incidences of dependency or death (mRS score of 3–6) at discharge and at the last follow-up were 16.7% and 14.3%, respectively. Aneurysm rebleeding occurred in one (3.3%) patient periprocedurally. In total, three (10.0%) patients had ischemic events, one of which occurred during the periprocedural period and two occurred during follow-up. A total of two patients (6.7%) underwent ventriculoperitoneal shunt. Imaging follow-up was available for 14 patients at the median of 12.0 (IQR, 7.0–12.3) months, with a complete occlusion rate of 93.3% (14/15). In total, one patient experienced parent artery occlusion, and no aneurysm was recanalized. Conclusion LVIS-within-enterprise double-stent technique with coil embolization for the treatment of patients with ari-VBDAs could be performed with a good safety profile and high technical success rate. The rate of complete aneurysm occlusion during follow-up seemed to be satisfactory.